2000
DOI: 10.1046/j.1365-313x.2000.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Allene oxide synthases of barley (Hordeum vulgare cv. Salome): tissue specific regulation in seedling development

Abstract: Summary Allene oxide synthase (AOS) is the first enzyme in the lipoxygenase (LOX) pathway which leads to formation of jasmonic acid (JA). Two full‐length cDNAs of AOS designated as AOS1 and AOS2, respectively, were isolated from barley (H. vulgare cv. Salome) leaves, which represent the first AOS clones from a monocotyledonous species. For AOS1, the open reading frame encompasses 1461 bp encoding a polypeptide of 487 amino acids with calculated molecular mass of 53.4 kDa and an isoelectric point of 9.3, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
0
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 162 publications
(138 citation statements)
references
References 72 publications
(111 reference statements)
9
122
0
7
Order By: Relevance
“…So far, all published data about the subcellular localization of AOS forms and AOS activity showed an association with chloroplast envelopes Maucher et al, 2000;Froehlich et al, 2001). This is in agreement with amino acid sequence data indicating that nearly all AOS proteins contain a putative chloroplast transit peptide.…”
Section: Subcellular Localization Of Staos3supporting
confidence: 87%
See 4 more Smart Citations
“…So far, all published data about the subcellular localization of AOS forms and AOS activity showed an association with chloroplast envelopes Maucher et al, 2000;Froehlich et al, 2001). This is in agreement with amino acid sequence data indicating that nearly all AOS proteins contain a putative chloroplast transit peptide.…”
Section: Subcellular Localization Of Staos3supporting
confidence: 87%
“…Most of them prefer 13-hydroperoxides as substrates and are involved in JA production. Immunocytochemical analysis in barley revealed the association of AOS with chloroplasts (Maucher et al, 2000) and confirmed the localization of AOS activity within chloroplass in spinach and tomato leaves Froehlich et al, 2001).…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations